(untitled) - Young, Burt; Shire, Talia; Avildsen, John G.; Stallone, Sylvester; 1935-2017 (Beverly Hills, California, 2014)
An unknown boxer from the slums of Philadelphia is given a once-in-a-lifetime shot at the world heavyweight title; Rock struggles to save his marriage while training for the championship rematch; Rocky loses his belt to an arrogant young fighter; Rocky challenges the Russian boxer who killed Apollo Creed in the ring.
Keywords: Balboa, Rocky; (Fictitious character); 1946-; Drama; Drama; Boxing; Drama; Boxers (Sports); Video recordings for the hearing impaired; Drama; Fiction films; Feature films; Sports films